IoT-Powered Customer Engagement for Marketing Optimization in Tanzania SMEs - Mkali, Khalifa Issa; Sinde, Ramadhani S.; Karokola, Geoffrey R. (Journal of Information System and Informatics, 2025)
Embracing Internet of Things (IoT) technologies presents significant opportunities for enhancing customer engagement. However, Tanzanian Small and Medium Enterprises (SMEs) are confronted with persistent challenges, including limited infrastructure, financial barriers, and low digital literacy. This study proposes an IoT-powered customer engagement platform built using Python-Django specifically tailored for Tanzanian SMEs to generate actionable customer insights and strengthen engagement strategies. A mixed-methods approach, combining surveys, observations, and interviews with SME owners and customers in Dar es Salaam and Arusha, revealed operational inefficiencies and gaps in customer interaction. Based on these insights, a scalable and cost-effective IoT solution was designed to automate feedback collection, monitor customer behavior in real-time, and deliver personalized services. The platform was evaluated through simulated testing, expert reviews, and performance analysis. Results showed a 15 - 20% improvement in customer retention, a 30% reduction in inquiry response time, 99.50% system uptime, and an 80% user-friendliness score. These findings demonstrate the novelty and effectiveness of integrating IoT, real-time monitoring, and marketing optimization in the Tanzania SME context. Overall, the research highlights the transformative potential of IoT in enabling data-driven decision-making, enhancing customer relationships, and promoting sustainable growth in underserved business environments.